Pelaksanaan Pembatalan Sertifikat Hak Atas Tanah Karena Cacat Administrasi dan Putusan Pengadilan di Kabupaten Lombok Timur - Yuliana, Yuliana (Fakultas Syariah INSURI Ponorogo, 2023)
Efforts to guarantee legal certainty and land legality apart from publish land certificates, also can be done by canceling land ownership certificates. In practice, it was found that a lot of land in East Lombok Reegency was still under disputed status. The discovery of administrative defects due to human error is efidence of non-compliance with the principle of land registration. This study aims to analyze the mechanism for cancellation of land ownership certificates due to administrative defects and court decisions at the National Land Agency Office in East Lombok Regency. Researchers apply normative juridical techniques with statutory approach. National Land Agency (BPN) has the authority to issue and cancel land rights in a concrete and final manner which causes legal consequences for both individual and legal entities. When a land title certificate is published, there is a possibility of administrative defects, and it can be canceled by a court decision as a party with permanent legal force. Conflict resolution disputes land in East Lombok Regency through legal measures has advantages and also disadvantages compared to negotiation and also mediation. Legal measures for disputes land in East Lombok can be used as an alternative conflict resolution involving indigenous peoples in order to maintain national security.